The limit between freedom of expression and hate speech: an analysis of the European Court of Human Rights judgements (Comillas Journal of International Relations, 2017)
The current situation in Europe and the Western world is to some extent a reflection of the latent conflict between the rise of hate speech and freedom of expression. Phenomena such as globalization and the increase of immigration to Europe have generated a wave of rejection and anxiety towards a changing reality, mainly due to aggravating factors such as the refugee crisis and terrorism. This trend highlights the debate about the limits of freedom of expression on the continent, a right that represents one of the most fundamental pillars of European democracies. In this way, this article analyses the state of the debate within the regional institutions, through a series of judgments from the European Court of Human Rights, to illustrate the current tug of war between freedom of expression and the limitation of hate speech.
Keywords: freedom of speech; European Court of Human Rights; hate speech